Allogeneic hematopoietic cell transplantation in Farber disease. Issue 2 (27th February 2019) - Ehlert, Karoline; Levade, Thierry; Di Rocco, Maja; Lanino, Edoardo; Albert, Michael H.; Führer, Monika; Jarisch, Andrea; Güngör, Tayfun; Ayuk, Francis; Vormoor, Josef
Abstract: Background: Farber disease (FD) is a rare, lysosomal storage disorder caused by deficient acid ceramidase activity. FD has long been considered a fatal disorder with death in the first three decades of life resulting either from respiratory insufficiency as a consequence of airway involvement or from progressive neurodegeneration because of nervous system involvement. Peripheral symptoms associated with FD, including inflammatory joint disease, have been described to improve relatively rapidly after hematopoietic cell transplantation (HCT). Aims: To evaluate the disease‐specific status and limitations in the long‐term follow‐up after HCT, investigate genotype/phenotype correlations and the benefit of allogeneic HCT in FD patients with nervous system involvement. Patients and methods: Transplant‐ and disease‐related information of ten FD patients was obtained by using a questionnaire, physicians' letters and additional telephone surveys. ASAH1 gene mutations were identified to search for genotype/phenotype correlations. Results: After mainly busulfan‐based preparative regimens, all patients engrafted with one late graft loss. The inflammatory symptoms resolved completely in all patients. Abnormal neurologic findings were present pre‐transplant in 4/10 patients, post‐transplant in 6/10 patients. Mutational analyses revealed new mutations in the ASAH1 gene and a broad diversity of phenotypes without a genotype/phenotype correlation. With a median follow‐up of 10.4 years, overall survival was 80% with two transplant‐related deaths. Conclusion: Allogeneic HCT leads to complete and persistent resolution of the inflammatory aspects in FD patients. It appears to have no beneficial effect on progression of nervous system involvement. New mutations in the acid ceramidase gene were identified. A genotype/phenotype correlation could not be established.